Votando con el changuito: la politización del consumo en América Latina - Echegaray, Fabián; Sarsfield, Rodolfo (Revista Latinoamericana de Opinión Pública, 2010)
Since the seminal work of Marshall (1950), the concept of citizenship has been mostly understood in “political-institutional “ terms. However, as corporations expand their role beyond economic and commercial matters and project themselves as agents of social and cultural change through their economic leverage and social responsibility initiatives, they reshape the notion of citizenship at the level of individuals. Thus, a relatively new process of politicization of consumer relationships with corporations impinges the need to stretch older interpretations of the category of citizenship. This paper intends to illustrate for three Latin-American countries how consumerism acquires a political nature by setting a tone for what is right and wrong in relation to companies ‘performance and by using ethical standards to influence corporate behavior. Finally, we aim at identifying the extent to which political consumerism may become a surrogate or a complement for standard, traditional ways to exercise citizenship through institutional channels.